(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
This research aims to develop mathematics student teacher professional and pedagogical competencies through subject Specific Pedagogy (SSP) workshops by applying cyclic-reflective-collaborative model. The research involved 42 mathematics student teacher of the Teacher Professional Education (PPG) program at the Department of Mathematics Education year 2015 and year 2016. The students had one year teaching experience. The workshops were carried out in 10 weeks, 6 cycles, using the design OXO, and focused on developing student abilities in planning educative learning-and-teaching (subject specific pedagogy)—which covers the following program: deepening subject matter knowledge, the development of learning methods and materials, the development of learning media and assessment tools, the development of teaching plans and syllabi, and the implementation of these components in the real classrooms. The strategy, used in the workshops, was a cyclic model: plan-action-reflection (PAR), which is adapted from the lesson study principles: plan-do-see. This strategy was implemented in a cycle of process, product, and open lesson. The instrument included professional and pedagogical competencies test—which covers school mathematics topics grades 7-12. The results showed that SSP workshops with cyclic model, applying the lesson study principles, are effective for developing student professional and pedagogical competencies—in medium level; most of students felt comfortable and were facilitated during the workshops; and the minimum competencies, quantitatively, can be achieved with the improvement is in the medium level.